Choosing a starting configuration for particle swarm optimization - RICHARDS, Mark; VENTURA, Dan (2004 IEEE International Joint Conference on Neural Networks (IEEE Cat. No.04CH37541), 2004)
The performance of particle swarm optimization can be improved by strategically selecting the starting positions of the particles. The work suggests the use of generators from centroidal Voronoi tessellations as the starting points for the swarm. The performance of swarms initialized with this method is compared with the standard PSO algorithm on several standard test functions. Results suggest that CVT initialization improves PSO performance in high dimensional spaces.